Effect of Dietary Gelatin Supplementation on the Expression of Selected Enterocyte Genes, Intestinal Development and Early Chick Performance - Fasina, Y.O.; Moran, E.T.; Ashwell, C.M.; Conner, D.E.; Leslie, M.; Mckee, S.R. (International Journal of Poultry Science, 2007)
Day-old Ross 308 chicks were used to evaluate the effect of dietary gelatin on intestinal development and broiler chick performance. Chicks were randomly allocated to two dietary treatments. The first treatment was the control SB diet based on corn-soybean meal and second treatment was the SBG test diet that contained 2% added gelatin with the total sulfur amino acid level remaining the same as in SB. Each treatment consisted of 4 replicate pens with 14 chicks per pen. Total duration of experiment was 0-3 weeks of age. Chick performance (weight gain and feed conversion efficiency) was evaluated on day 7 and 14. To assess intestinal development, abundance of mRNA of selected enterocyte genes (alkaline phosphatase, leucine aminopeptidase and mucin) was quantitatively determined by RT-PCR on day 7. Biochemical indices including DNA concentration, protein:DNA and protein:RNA ratios were also used to assess intestinal development. Results indicated that chicks fed the SBG diet had improved feed conversion efficiency on day 7 (p